Optimal Exit Configuration of Factory Layout for a Safer Emergency Evacuation using Crowd Simulation Model and Multi-Objective Artificial Bee Colony Optimization - Khamis, Nurulaqilla; Selamat, Hazlina; Ismail, Fatimah Sham; Lutfy, Omar Farouq (International Journal of Integrated Engineering, 2019)
This work aims at providing a systematic method in producing a safer and optimal factory layout based on a crowd simulation model and the multi-objective artificial bee colony optimization technique. Apart, from ensuring the efficiency of manufacturing processes in planning a factory layout, it is also important that the safety aspect is taken into account. A factory is usually a closed working area consisting of machines, equipment, assembly lines as well as individual working space and other departments within the factory. In this environment, workers move around in the factory to perform different activities, and hence highly complex crowd behaviours that are influenced by the physical, social and psychological factors of the crowd might take place. Therefore, the layout of the factory must be carefully designed so that efficient movements of people can be obtained. Furthermore, during emergency situations that require efficient evacuation of workers from the factory building, a good factory layout will prevent or minimize the possibility of injuries during the evacuation process. This will reduce the evacuation egress time, which is the quantity used to evaluate the evacuation efficiency and the building’s level of safety. One of the techniques to assess the evacuation efficiency of a particular space configuration is by using the crowd simulation model. Recent evidences suggest that the representation of crowd dynamics using a simulation model is useful, where experiments with real humans are too dangerous and not practical to be implemented. This work explains the method to provide optimal exit door configurations for a factory layout by analyzing the crowd evacuation time and the discomfort level, where the proposed optimum exit configurations will be compared with the original configuration for a better evacuation efficiency.